A crítica e o artista: samba, repressão e poesia em Chico Buarque - Bonis, Maria Luísa Rangel De (2005)
The aim of this work is to analyze a body of critical reviews and other journalistic writings produced at two different moments of Chico Buarque s career: early 1970 s and early 1990 s. For this purpose, we have chosen three specific works to be studied: Sinal fechado (1974), Francisco (1987), and Paratodos (1993). In the analyses of reviews published on major magazines and newspapers from São Paulo and Rio de Janeiro about the chosen productions, our research tried to understand the way both work and artist were interpreted. Cultural criticism, here, is a first step on the way to understand the social and cultural scene of the focused periods. With this in mind, we looked for a theoretical foundation in authors such as Theodor W. Adorno and Walter Benjamin. For the study of Chico Buarque s songs, other authors such as Antonio Candido, Haroldo de Campos, Roberto Schwarz, and Sergio Buarque de Hollanda are sources which bring out important ways of interpreting the Brazilian reality. Thus, our theoretic foundation is related to authors who understand Brazil beyond the specific domain of criticism, and who point out new perspectives for its interpretation. The main conclusion of this study is the realization that cultural criticism plays a fundamental role in the way Chico Buarque s songs are understood at the moment of their production. Beginning with criticism, through historical and political contexts, every work assumes aspects that qualify it. And its from criticism, that some fundamental elements for its own understanding samba, poetry and political repression are questioned